Data-driven marketing content : a practical guide - Wilson, Lee (Emerald Publishing Limited, 2019)
In the world we live in today, more data is being generated than at any other period in human history. However, this wealth of information is causing a data dilemma for small to medium sized enterprises (SMEs), entrepreneurs, and practitioners. With marketing companies and experts struggling to produce business content that delivers strong marketing results and SME's being overshadowed by data-aware super-brands that are already heavily investing in data-driven content, Lee Wilson offers a solution that can rectify the performance divide.Data-Driven Marketing Content: A Practical Guide empowers businesses, regardless of industry, size, or competition level, to understand, identify and act on big-data opportunities. The guide shares unique processes, approaches, and frameworks which can be applied to every company need, leading you towards efficient and effective content creation that repeatedly returns on investment. Through a combination of practical expertise and personal insights, this book instructs and enables practitioners and entrepreneurs to overcome everyday business content barriers and yield increased results from every piece of content created. - Resumé vydavatel
Keywords: marketingový výzkum; zpracování dat; marketing; malé a střední podniky; marketing research; data processing; small and medium-sized enterprises; elektronické knihy; příručky; electronic books; handbooks and manuals